Upaya Membangun Masyarakat Ekonomi Kreatif Melalui Kesenian Tradisional Di Era Asean Community - Harini, Setyasih; Hapsari, Alfonsa Maria Sofia (Journal of Social and Political Science, 2017)
Indonesia has various culture but local culture faced serious threats in globalization era. In globalization, rapid development of information and communication technology has transfered from industrialized or developed countries into developing countries.The developed countries used information and communication technology to transfer culture too. Problematically this culture doesnât match with basic values of Indonesia. This rapid development has negative impact specially for teenager. Participation of teenager in local art was important to preserve local culture and increase nationalism. Unfortunately, this teenager less participated in that practice. It could cause of identity crisis. Purpose of this research to explain effort of Sanggar Tari Edi Peni and Sanggar Ketoprak Lelono Langen Budoyo. This effort related with increasing nationalism of teenager with traditional art. After training and monitoring activity, students of Sanggar Tari Edi Peni and Sanggar Ketoprak Lelono Langen Budoyo more loved with local art, increase their nationalism, and ready to make their own creativity and completed their Website. This Website will be a tool to promote information and activity of Sanggar Tari Edi Peni and Sanggar Ketoprak Lelono Langen Budoyo. It showed that teenager of Sanggar Tari Edi Peni and Sanggar Ketoprak Lelono Langen Budoyo could make indutrial economy society and also ready to face ASEAN Socio-Cultural Community.   Key words: nationalism, teenager, ASEAN Socio-Cultural Community